Using historical sources to supplement climate site histories: A case study of Auckland's Albert Park. (5th August 2020) - Fowler, Anthony M.
Abstract: New Zealand's best‐known record of surface air temperature is the partially homogenised seven‐station series of the National Institute of Water and Atmospheric Research. The homogeneity analysis used in constructing this series depends on the completeness of the site histories and issues arise if relevant information is missing. Recent developments in the online availability of searchable historical records provide an opportunity to supplement early metadata. This potential is explored here using Albert Park (Auckland) as a case study. A wealth of relevant historical information about Albert Park was found in online archives, especially related to a major episode of site disturbance, evolving site environment and instrumentation changes.